2013
DOI: 10.1002/pola.26670
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of resorcinarene‐centered amphiphilic A8B4 miktoarm star copolymers based on poly(ε‐caprolactone) and poly(ethylene glycol) by combination of CROP and “click” chemistry

Abstract: Well‐defined amphiphilic A8B4 miktoarm star copolymers with eight poly(ethylene glycol) chains and four poly(ε‐caprolactone) arms (R‐8PEG‐4PCL) were prepared using “click” reaction strategy and controlled ring‐opening polymerization (CROP). First, multi‐functional precursor (R‐8N3‐4OH) with eight azides and four hydroxyls was synthesized based on the derivatization of resorcinarene. Then eight‐PEG‐arm star polymer (R‐8PEG‐4OH) was prepared through “click” reaction of R‐8N3‐4OH with pre‐synthesized alkyne‐termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Click couplings, especially the copper-catalyzed azide–alkyne cycloaddition, but also thiol–ene and Diels–Alder reactions, have been identified as a convenient method to attach prefabricated PEG chains. Since click reactions take place under mild conditions and tolerate a great amount of functional groups, they have found to be particularly useful for the preparation of miktoarm stars. Controlled radical polymerization techniques, such as ARTP and RAFT, have also been explored extensively as a synthetic tool for arm-first star polymer synthesis. After end functionalizing PEG with a suitable initiator group, cross-linking polymerization of divinyl monomers leads to star architectures. In analogy, ring-opening metathesis polymerization was applied using bis-norbonene monomers .…”
Section: Star-shaped and Hyperbranched Poly(alkylene Oxides)mentioning
confidence: 99%
“…Click couplings, especially the copper-catalyzed azide–alkyne cycloaddition, but also thiol–ene and Diels–Alder reactions, have been identified as a convenient method to attach prefabricated PEG chains. Since click reactions take place under mild conditions and tolerate a great amount of functional groups, they have found to be particularly useful for the preparation of miktoarm stars. Controlled radical polymerization techniques, such as ARTP and RAFT, have also been explored extensively as a synthetic tool for arm-first star polymer synthesis. After end functionalizing PEG with a suitable initiator group, cross-linking polymerization of divinyl monomers leads to star architectures. In analogy, ring-opening metathesis polymerization was applied using bis-norbonene monomers .…”
Section: Star-shaped and Hyperbranched Poly(alkylene Oxides)mentioning
confidence: 99%
“…[21][22][23][24][25] As typical biomaterials approved by the United States Food and Drug Administration (FDA), 26,27 poly-(ethylene glycol) (PEG) and poly(ε-caprolactone) (PCL) have been widely used to construct amphiphilic copolymers, such as diblock, 28,29 triblock, 30,31 three-armed, 32 four-armed 32,33 and multi-armed star-shaped copolymers. [34][35][36][37] In 2012, Hawker et al reported a convenient one-step way to simultaneously introduce functional acetal and azide groups in the same polymer chain, 19 which provides us more opportunities to prepare pH-responsive polymers by means of a highly efficient CuAAC "Click" reaction. Our group has recently utilized this method for preparing a pH-sensitive triblock copolymer PCL-a-PEG-a-PCL, in which the acetal groups can be rapidly acid-triggered for hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Poly( ε ‐caprolactone)s (PCLs), which have been studied extensively over the past 20 years, are one of the most attractive biocompatible and biodegradable polyesters . PCLs low glass transition temperature, low melting temperature, and high miscibility with commercial polymers compared with other polyesters provide significant advantages to the use of PCLs in absorbable sutures, surgical fibers, artificial organs, controlled drug delivery applications, tissue regeneration approaches, food packages, and PVC plasticizers . PCLs are produced via the ring‐opening polymerization (ROP) of the cyclic ester monomer, ε ‐caprolactone (CL).…”
Section: Introductionmentioning
confidence: 99%